Kemampuan Koneksi Matematika Siswa Dalam Menyelesaikan Soal Matematika Bentuk Cerita Ditinjau Dari Kemampuan Awal Matematika Siswa SMP Negeri 1 Majene - Amran Yahya (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2018)
The type of this research is descriptive research that aims to determine the ability of students mathematical connections to solve the problem of story form on Triangle and Triangle material in class VII of SMP Negeri 1 Majene based on students' early math ability. The subjects of the study were 6 students consisting of 2 students with a high level of early math ability, 2 students with moderate level of math ability, and 2 students with low level of early math ability. The result of the research shows that (1) students with high level of high mathematics ability have high mathematical connection ability, students with high ability level can solve problems and connect them with mathematics, science (other), and daily life well. But there are students who have little problem in solving the problem (2) students with the basic level of mathematics skills have medium math connection ability, students with ability level are able to understand the problem, but have difficulty in solving the problem and connect it with mathematics concept, fields), and daily life. (3) students with low level of early math ability have low mathematical connection ability, Students with low ability level have difficulty in understanding determine the elements of the problem so that they can not solve the problem and connect it with mathematics, science (other), and also everyday life.